Metabolic regulation of Th9 cell differentiation: insights for IL-9-driven diseases - Peesari, Swetha; McAleer, Jeremy P. (Frontiers in Immunology, 2025)
Th9 cells are a CD4 T cell subset that produces interleukin-9 (IL-9), a pleiotropic cytokine implicated in allergies, autoimmunity and cancer. Defining the cellular effects of IL-9 and factors regulating its expression are essential for fully understanding its roles in immunity and disease. IL-9 acts on a variety of immune and non-immune cells through a heterodimeric receptor composed of IL-9Rα and the common gamma chain. In CD4 T cells, IL-9 promotes mTOR activation, aerobic glycolysis, proliferation and reinforces its own expression. Additional cellular effects include mast cell activation, B cell antibody production and anti-tumor immunity. These biological activities are complemented by recent studies that expand our understanding of Th9 differentiation beyond canonical cytokine and transcription factor pathways. Notably, glycolytic reprogramming and fatty acid metabolism have emerged as key regulators of IL-9 production, mediated through the activities of mTOR, PPAR-γ and acetyl-CoA carboxylase 1 (ACC1). mTOR-driven aerobic glycolysis is essential for Th9 cell differentiation, supporting survival, proliferation, and IL9 expression through HIF-1α activation. In contrast, ACC1 suppresses IL-9 through fatty acid synthesis, which enhances RARα-mediated transcriptional repression. PPAR-γ appears to have dual functions: it promotes IL-9 production by increasing glucose uptake and activating mTOR, but reduces IL-9 in response to synthetic agonists that may increase fatty acid uptake. Overall, these findings highlight critical roles for metabolic regulators in Th9 responses and suggest that targeting these pathways may offer new therapeutic strategies for IL-9-driven diseases.